Environmental sustainability in milk-producing family farms in the micro-region of Carazinho-RS - Mattei, Adriano; Rempel, Claudete; Maciel, Mônica Jachetti (Ciência e Natura, 2022)
Milk production in the northwestern region of Rio Grande do Sul has been particularly prominent among family farmers. Given the need to diversify production in their small farms, family farmers consider dairy farming a potential alternative to increase family income. However, the environmental dimension is often sidelined when implementing or maintaining this agricultural activity. Therefore, the aim of the present study was to evaluate the environmental sustainability of milk-producing family farms in the microregion of Carazinho-RS in order to identify the environmental reality in these properties. A total of 167 properties were sampled from the ten municipalities that have the most significant dairy production in the microregion. The environmental sustainability index of the properties was identified by applying a questionnaire. Research results showed that the microregion studied has a regular environmental sustainability index. This indicates the need for some adjustments, mainly in the indicators ‘land use’ and ‘legal reserve’, which were the ones that most compromised their environmental sustainability index.